Conditional IL-2 Gene Deletion: Consequences for T Cell Proliferation - Smith, Kendall A.; Popmihajlov, Zoran; Xu, Dong; Morgan, Heather; Milligan, Zoie (Frontiers in Immunology, 2012)
To explore the role of interleukin-2 (IL-2) in T cell proliferation, and to circumvent the IL-2 deficiency autoimmune syndrome of conventional il2 gene deletion, mice were created to allow conditional il2 gene deletion when treated with the estrogen analogue, tamoxifen (TAM) as adults. Splenocytes from four different mouse strains, C57Bl/6 wild type (WT), conventional IL-2 (-/-), TAM-treated Cre recombinase negative (Cre-)/IL2fl/fl, and Cre+/IL-2fl/fl (Cre+), were activated with anti-CD3 and anti-CD28, and monitored for CD4+ and CD8+ T cell lymphocyte blastogenesis, aerobic glycolysis, BrdU incorporation into newly synthesized DNA, and CFSE dye dilution to monitor cell division. IL-2 production was monitored by quantitative ELISA and multiple additional cytokines were monitored by protein-bead arrays. Splenocytes from conventional IL-2 (-/-) and TAM-treated Cre+ mice resulted in undetectable IL-2 production, so that both strains were IL-2 deficient. As monitored by flow cytometry, activated CD4+ and CD8+ T cells from WT, Cre+ and Cre- mice all underwent blastogenesis, whereas far fewer cells from conventional IL-2 (-/-) mice did so. By comparison, only cells from IL-2 sufficient WT and Cre- switched to aerobic glycolysis as evidenced by a drop in media pH. Blastogenesis was mirrored by BrdU incorporation and CFSE dye dilution by CD4+ and CD8+ T cells from WT, Cre+ and Cre- mice, which were all equivalent, while proliferation of cells from conventional IL-2 (-/-) mice was compromised. Splenocytes from IL-2 deficient conventional IL-2 (-/-) mice produced low or undetectable other γc-chain cytokines (IL-4, IL-7, IL-9, IL-13, IL-15, and IL-21), whereas production of these γc-chain cytokines from IL-2-deficient conditional IL-2 (-/-) Cre+ mice were comparable with WT and Cre- mice. These results indicate that CD4+ and CD8+ T cell blastogenesis cannot be attributable to IL-2 alone, but a switch to aerobic glycolysis is attributable to IL-2, and proliferation after CD3/CD